2021
DOI: 10.1177/03000605211037495
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA CASC9 alleviates lipopolysaccharide-induced acute kidney injury by regulating the miR-424-5p/TXNIP pathway

Abstract: Objective This study aimed to clarify the mechanism by which the long non-coding RNA cancer susceptibility candidate 9 (CASC9) alleviates sepsis-related acute kidney injury (S-AKI). Methods A lipopolysaccharide (LPS)-induced AKI model was established to simulate S-AKI. HK-2 human renal tubular epithelial cells were treated with LPS to establish an in vitro model, and mice were intraperitoneally injected with LPS to generate an in vivo model. Subsequently, the mRNA expression of inflammatory and antioxidant fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…In an effort to evaluate the role of miR-424 in oxidative stress accumulation, an miR-424 inhibitor was applied, and we showed that ROS generation was suppressed. Our findings were consistent with another study showing that miR-424 conferred to the LPS-induced ROS production in lipopolysaccharide (LPS)-treated pulmonary alveolar epithelial cells [ 29 ] or LPS-stimulated proximal tubule epithelial cells [ 30 ]. However, miR-424 was revealed to abrogate oxidative stress-associated injury by increasing antioxidant enzymes and reducing oxidative stress indicators in C57/BL6 mice with transient cerebral ischemia [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…In an effort to evaluate the role of miR-424 in oxidative stress accumulation, an miR-424 inhibitor was applied, and we showed that ROS generation was suppressed. Our findings were consistent with another study showing that miR-424 conferred to the LPS-induced ROS production in lipopolysaccharide (LPS)-treated pulmonary alveolar epithelial cells [ 29 ] or LPS-stimulated proximal tubule epithelial cells [ 30 ]. However, miR-424 was revealed to abrogate oxidative stress-associated injury by increasing antioxidant enzymes and reducing oxidative stress indicators in C57/BL6 mice with transient cerebral ischemia [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…These 500 samples were then added to the LIME explainer and input to the HGC-GAN for prediction to assess the contribution level of the features. Through model predictions, the disease with the highest associated probability with CASC9 was identified as Acute Kidney Failure, and this association prediction has been confirmed [ 39 ]. Therefore, we conducted experimental analysis on the association between CASC9 and Acute Kidney Failure.…”
Section: Resultsmentioning
confidence: 96%
“…Wang et al found that XIST acts as a ceRNA for miRNA-155-5p to suppress inflammation and apoptosis, thereby attenuating sepsis-induced AKI( Wang and Cao, 2022 ). Furthermore, Fan et al found that the CASC9 could attenuate LPS-induced acute renal inflammatory injury via the miRNA-424-5p/TXNIP axis ( Fan et al, 2021 ). The latest research showed that NORAD knockdown alleviated kidney injury in mice and decreased the inflammatory response and apoptosis of LPS-stimulated HK-2 cells via the miRNA-577/GOLPH3 axis ( Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%